Ventricular Tachycardia from a Central Line Fracture Fragment Embolus: A Rare Complication of a Commonly Used Procedure—A Case Report and Review of the Relevant Literature - Saptarshi Biswas; Patrick McNerney (Case Reports in Critical Care)
A 22-year-old male admitted with multiple gunshot wounds (GSW) had central line placed initially for hemodynamic monitoring and later for long term antibiotics and total parenteral nutrition (TPN). On postoperative day 4 he presented with bouts of nonsustained ventricular tachycardia; the cause was unknown initially and later attributed to a catheter fragment accidentally severed and lodged in the right heart. Percutaneous retrieval technique was used to successfully extract the catheter fragment and complete recovery was achieved.